EARLY CHILDHOOD CARIES AND ITS RELATIONSHIP WITH DIFFERENT RISK FACTORS IN PRESCHOOL CHILDREN - Saleem, Urooj; Bibi, Saeeda; Jamil, Brekhna (Journal of Postgraduate Medical Institute, 2015)
Objective: To find the frequency/pattern of Early Childhood caries (ECC) andto find out the relationship of different risk factors with ECC. Methodology: A cross sectional survey was conducted in both pediatric departmentspresent in the dental hospitals of Peshawar, Pakistan from August2013 to January 2014 . All children with age range of 3- 6 years that visitedpediatric department were selected. The diagnosis of ECC was solely based onclinical assessment. A parent or a caregiver was asked to complete a questionnaire regarding information about the child, their oral hygiene, demographicsand feeding practices. The data was arranged categorically and analyzed usingStatistical Package of Social Sciences (SPSS 16). Chi Square test was usedto calculate statistical significance set at <0.05. Results: A total number of 320 children were selected. The Mean age of oursample was 4.2 +1.14 years Majority of children were males (n=184, 57.5%)while females were (n=136, 42.5%) The frequency of Early Childhood Carieswas 85 %(272). Anterior teeth had more caries (n=139, 43.4%) than posteriorand upper jaw teeth had more caries (n=171, 53.4%) than lower jaw. Feedinghabits, Age, mother's age, adult supervision, and knowledge of parent werefound to be significantly related with Early Childhood Caries (p<.005), whilethe gender and who applies the tooth paste were found not significant. Conclusion: There is a high occurrence of early child hood caries amongchildren visiting dental hospitals in Peshawar. Anterior upper teeth are moreprone to caries.